Assessing the effectiveness of group motivational interviewing in raising awareness of mobile gaming addiction among medical students : a pilot study - Leonard Li, Yik Chuan; Chen, Yoke Yong; Chai, Chee Shee; Chew, Keng Sheng (BioMed Central Ltd., 2025)
Objective